2022
DOI: 10.3390/biomedicines10071470
|View full text |Cite
|
Sign up to set email alerts
|

An Oral 3D Printed PLGA-Tocopherol PEG Succinate Nanocomposite Hydrogel for High-Dose Methotrexate Delivery in Maintenance Chemotherapy

Abstract: High-dose methotrexate (HDMTX) is one of the chemotherapeutic agents used to treat a variety of cancers in both adults and children. However, the toxicity associated with HDMTX has resulted in the spread of infections and treatment interruption. Further, poor bioavailability due to efflux pump activities mediated by P-glycoprotein has also been linked to poor therapeutic effects of methotrexate following oral administrations. D-α-Tocopheryl poly-ethylene glycol 1000 succinate (TPGS) is known to improve the bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…A work focusing on the fabrication of methotrexate-loaded nanoparticles fixed in alginate-gelatine 3D printable hydrogel ink to produce a solid 3D printed tablet for oral administration was published by a researcher. The results showed that a 25 G needle was used to produce great precision (> 95%) of the 3D printed tablets, and drug release patterns were evaluated in vitro at pH 1.2 and pH 7.4 to imitate the gastrointestinal environment [50]. Research reported that 3D printing technology has been widely explored for the rapid design and fabrication of hydrogels, as required by complicated soft structures and devices.…”
Section: Fabrication Of Nanogels Using 3d Printing Technologiesmentioning
confidence: 99%
“…A work focusing on the fabrication of methotrexate-loaded nanoparticles fixed in alginate-gelatine 3D printable hydrogel ink to produce a solid 3D printed tablet for oral administration was published by a researcher. The results showed that a 25 G needle was used to produce great precision (> 95%) of the 3D printed tablets, and drug release patterns were evaluated in vitro at pH 1.2 and pH 7.4 to imitate the gastrointestinal environment [50]. Research reported that 3D printing technology has been widely explored for the rapid design and fabrication of hydrogels, as required by complicated soft structures and devices.…”
Section: Fabrication Of Nanogels Using 3d Printing Technologiesmentioning
confidence: 99%